Optimal Resource Provision of Cloud Center with Guarantee Percentile Response Time - Huaiwen He (Dianxin kexue)
In order to minimize resource provisioning cost of commercial cloud center，while guarantee percentile response time SLA，a cloud center model based on queuing theory was proposed.Resource provisioning cost was analyzed from an economic point of view，and the mathematical expressions of cloud center percentile response time were deduced.Meanwhile the minimum provisioning cost algorithm（MPCA）was developed to calculate the minimum cost of cloud center，the affect on cloud center cost by load flow，percentile response time and based response time was analyzed via a large number of experiments.The results show that with MPCA to optimized server number and speed of cloud center，it can achieve cost linear increase with increasing traffic load.